“Tudung lingkup”, the Malay woman’s clothing in Seberang Jambi City - Wita, Gusmira; Mursal, Irhas Fansuri; Wirdanengsih, Wirdanengsih (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2023)
The “Tudung lingkup” is one of the clothes worn by Malay women in Seberang Kota Jambi. The “tudung lingkup” has been present in the midst of Jambi society since Islam entered Jambi through Chinese, Arab and Turkish traders. The “tudung lingkup” has also become a cultural identity for the Islamic community in Seberang Kota Jambi. At present, “tudung lingkup” has become a cultural tour through the “tudung lingkup” festivals. This study aims to describe the “tudung lingkup” which is the identity of Jambi Malay women in Seberang Jambi City and the potential of the tudung lingkup as a cultural tourism object in Seberang Kota Jambi. This research is qualitative research with data collection through interviews, observation and document analysis. Analysis of research data was carried out through the stages of data reduction, data display and verification/conclusions. The triangulation technique is used to determine the validity of the research data. This study shows that: (1) Malay women in Seberang Kota Jambi make the “tudung lingkup” as a cover for their private parts as adaptation to Islamic culture, (3) the “tudung lingkup” represents the characteristics of Arab-Malay culture di Seberang Kota Jambi and the ability of Jambi Malay women to adapt to Islamic culture, and (4) the “tudung lingkup” is rarely found in the people of Seberang Kota Jambi so that festivals of “tudung lingkup” as cultural tourism to preserve the local wisdom of the people of Seberang Kota Jambi and develop Jambi batik crafts